Prevalence and risk factors of vascular complications in type 2 diabetes mellitus: Results from discover Middle East and Africa cohort - Hafidh, Khadija; Malek, Rachid; Al-Rubeaan, Khalid; Kok, Adri; Bayram, Fahri; Echtay, Akram; Rajadhyaksha, Viraj; Hadaoui, Ahmed (Frontiers in Endocrinology, 2022)
Background We evaluated the prevalence of vascular complications and associated risk factors in individuals with type 2 diabetes mellitus (T2DM) initiating second-line glucose-lowering therapy from the Middle East and Africa (MEA) cohort of the 3-year prospective DISCOVER study involving 15,992 patients in 38 countries. Methods Baseline cross-sectional data collected from healthcare settings were used to assess micro and macrovascular complications prevalence as crude and age- and sex-standardised. The multi‐variable analysis assessed factors associated with these complications. Results Of 3,525 enrolled patients (mean age: 54.3 ± 10.8 years), >40% had hypertension and hyperlipidaemia. Metformin monotherapy was the first-line therapy in 56.5%, followed by metformin+sulphonylurea (20.3%). Crude and standardised prevalence of microvascular complications were 17.7% and 16.9% (95% confidence interval [CI], 16.77‐16.98) and macrovascular complications were 10.7% and 8.7% (95% CI, 8.59–8.76). Factors significantly (p<0.05) associated with micro and macrovascular complications (odds ratios [95% CI]) were age (1.24 [1.12–1.39] and 1.58 [1.35–1.84]), male sex (1.33 [1.04‐1.70] and 1.71 [1.22–2.40]), hyperlipidaemia (1.33 [1.07-1.65] and 1.96 [1.46-2.63]) and hypertension (1.75 [1.40–2.19] and 2.84 [2.07-3.92]). Conclusion A substantial burden of vascular complications with prominent risk factors in the MEA cohort calls for early preventive interventions.